Synthesis of salicylic acid from wintergreen oil by green chemistry overcomes its cytotoxicity in keratinocyte cells and teratogenicity in zebrafish embryos - ALTURFAN, EBRU IŞIK (My University, 2023)
Salicylic acid topical is used to treat variety of skin conditions. However, salicylic acid in these products is generated through industrial synthesis and has been shown to negatively impact fetal development and cause congenital abnormalities. We hypothesized that teratogenic effects reported in salicylic acid can be prevented by naturally synthesizing salicylic acid from wintergreen oil using green chemistry method. For this purpose, we investigated the effects of natural salicylic acid (NSA) synthesized from wintergreen oil using green chemistry and synthetic salicylic acid (SSA) on keratinocyte cell (HaCaT) proliferation and zebrafish embryo development. NSA structures were analyzed by 1 H NMR, 13C NMR, and GC/MS methods. Percentage inhibition against HaCaT cell was determined by MTS assay. xCelligence system was used for cellular activities. Zebrafish embryos were exposed to NSA and SSA for 72 h post-fertilization. Lipid peroxidation, nitric oxide, sialic acid, glutathione-S-transferase, catalase, and superoxide dismutase were evaluated using biochemical methods. Expressions of nqO1, gfap, bdnf, vtg, egr, cyp1a, and igf2 were determined by RT-PCR as developmental indicators. MTS and RTcell analysis showed increased cell viability by NSA, whereas SSA decreased cell viability. NSA beneficially affected zebrafish embryo development while SSA exerted deleterious effects through oxidant– antioxidant status, inflammation, and development. Results of our study showed for the first time that synthesis of salicylic acid from wintergreen oil by green chemistry overcomes its cytotoxicity in keratinocyte cells and teratogenicity in zebrafish embryos. This finding is important for drug research on safe topical applications during pregnancy, when preventing exposure to drug and chemical-derived teratogens is vital.
Keywords: Salicylic acid; wintergreen oil; green chemistry; zebrafish embryo toxicity; cell proliferation